1981
DOI: 10.1136/jcp.34.12.1333
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells in the human alveolar wall: an electronmicroscopic study.

Abstract: SUMMARY Mast cells were identified by electronmicroscopy in the alveolar wall of the lung in 20 subjects (10 normal, 10 abnormal). A quantitative and qualitative study was made of the mast cells. In the normal lung there was an average concentration of 350 mast cells/mm2 of alveolar wall and in the abnormal 523/mm2. Mast cells occupied approximately 1-6-2-1 % of the area of the alveolar wall. There was marked variation in the structure of the mast cell granules but no differences between those in the normal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0
2

Year Published

1986
1986
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 10 publications
5
27
0
2
Order By: Relevance
“…Mast cells are abundant in the lung, occupying ϳ1.6 -2.1% of the area of the alveolar wall (36). Importantly, many human lung mast cells directly protrude through the alveolar wall into air space (36), which allows direct interaction between mast cells and pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mast cells are abundant in the lung, occupying ϳ1.6 -2.1% of the area of the alveolar wall (36). Importantly, many human lung mast cells directly protrude through the alveolar wall into air space (36), which allows direct interaction between mast cells and pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells are abundant in the lung, occupying ϳ1.6 -2.1% of the area of the alveolar wall (36). Importantly, many human lung mast cells directly protrude through the alveolar wall into air space (36), which allows direct interaction between mast cells and pathogens. Recently, we demonstrated active interactions between human mast cells and P. aeruginosa, resulting in the secretion of mast cell-derived cytokines and chemokines that are important in innate immunity (37 -FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Increase of mast cells in the peribronchiolar space and adjacent to the interalveolar septa in lung of mice in our experiments, probably contributes to the permeability changes seen in this organ. Tissue mast cells probably are activated and also involved in DEN injury, since they are usually found in normal and abnormal alveolar wall (Fox et al 1981). They produce a series of vasoactive mediators, including histamine and histamine-like products.…”
Section: Discussionmentioning
confidence: 99%
“…However, in normal lung we observed more (64-2%) granules of 'scroll'and 'combined'type, while in asthmatic lung the majority (59-7%) of granules were 'particulate' or 'empty'. If we accept the hypothesis that during the mediators release the structure of mast cell granules changes from 'scroll' and 'combined' to 'particulate' and 'empty' (Trotter and Orr, 1973;Kawanami et aL, 1979;Fox et al, 1981), then our data suggest that the degranulation process is more marked in asthmatic tissue than in normal. This contradicts the data obtained by Fox and associates (1981), who found that the scale of degranulation was the same in normal and pathological lung tissue, but supports the findings of Connell (1971) and Kawanami and co-workers (1979) that degranulation is more common in pathological than in normal lung.…”
Section: Discussionmentioning
confidence: 86%
“…While most studies of pulmonary mast cells have concentrated on their presence in the bronchial tree (Connell, 1971;Patterson and Suszko, 1971;Austen and Orange, 1975;Jeffery and Corrin, 1984), recent studies have shown that mast cells are also present in alveolar structures (Kawanami et al, 1979;Fox, Bull and Guz, 1981;Agius et ai, 1984;Tomioka et al, 1984). However, very little data on mast cell content and structure within the alveolar wall in normal and diseased lung are available.…”
Section: Introductionmentioning
confidence: 99%